Preservation of Cultural Values and Religious Character Through the Art of Gembyung Art - Fendry Abdul Mubaroq; Sapriya Sapriya; Sri Wahyuni Tanzil (Department of Civic Education, 2021)
The cultural diversity that is owned by the Indonesian nation is a beautiful thing to be maintained and preserved so that it has an important role in building good relations in the progress of the nation. As a good citizen, one must maintain and preserve every culture that belongs to the Indonesian state. One of the cultures that Indonesia has is the Gembyung culture, which originates from Sumedang, West Java. In this study, researchers used a qualitative approach with the case study method. The participants in this study were the Sumedang Regency heirloom group with data collection techniques through interviews, observations and literature studies. The data analysis technique used is data reduction, data presentation and conclusions drawn by researchers. The results obtained from this study are: (1) Knowing the art form of gembyung in Sumedang Regency to preserve culture and religious character, (2) Management of Gembyung art in Sumedang Regency in preserving cultural values and religious character, (3) constraints and solutions in managing gembyung art in Sumedang Regency in preserving cultural values and religious character.